Short-term perioperative outcomes of patients treated with radical cystectomy for bladder cancer included in the National Surgical Quality Improvement Program (NSQIP) database - Gandaglia, Giorgio; Varda, Briony; Sood, Akshay; Pucheril, Daniel; Konijeti, Ramdev; Sammon, Jesse D; Sukumar, Shyam; Menon, Mani; Sun, Maxine; Chang, Steven L; et al. (Canadian Urological Association Journal, 2014)
Introduction: We report the contemporary outcomes of radical cystectomy (RC) in patients with bladder cancer using a national, prospective perioperative database specifically developed to assess the quality of surgical care. Methods: The National Surgical Quality Improvement Program (NSQIP) database was queried from 2006 to 2011 for RC. Data on postoperative complications, operative time, length of stay, blood transfusions, readmission, and mortality within 30 days from surgery were abstracted. Results: Overall, 1094 patients undergoing RC were identified. Rates of overall complications, transfusions, prolonged length of hospitalization, readmission, and perioperative mortality were 31.1%, 34.4%, 25.9%, 20.2%, and 2.7%, respectively. Body mass index represented an independent predictor of overall complications on multivariate analysis (p = 0.04). Baseline comorbidity status was associated with increased odds of postoperative complications, prolonged operative time, transfusion, prolonged hospitalization, and perioperative mortality. In particular, patients with cardiovascular comorbidities were 2.4 times more likely to die within 30 days following cystectomy compared to their healthier counterparts (p = 0.04). Men had lower odds of prolonged operative time and blood transfusions (p ≤ 0.03). Finally, the receipt of a continent urinary diversion was the only predictor of readmission (p = 0.02). Our results are limited by their retrospective nature and by the lack of adjustment for hospital and tumour volume. Conclusions: Complications, transfusions, readmission, and perioperative mortality remain relatively common events in patients undergoing RC for bladder cancer. In an era where many advocate the need for prospective multi-institutional data collection as a means of improving quality of care, our study provides data on short-term outcomes after RC from a national quality improvement initiative.